Origins and development of the laesio enormis and the fair price doctrine - Salazar Santander, Arturo (Derecho Público Iberoamericano, 2020)
Laesio enormis, through its complex history and development, from postclassic Roman law to modern instruments of uniform law, has been the great institution that guarantees the justice of exchanges of contractual agreement. It has been questioned and reinterpreted, expanded and restricted on numerous occasions, but the material justice substratum, beyond the agreement of wills, is what has remained stable. However, in legal systems, which took the model of the Napoleon Code, it is a problematic institution with the autonomy of the will and the pacta sunt servanda. On the other hand, those systems that give it a broad provenance can clearly recognize the concretion of the principle of contractual equilibrium as a requirement of objective good faith and fairness.